Power Quality in Microgrids Based on Distributed Generators - Chandra, Ambrish (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book comprises ten articles covering different aspects of power quality issues in microgrids and distributed generation (DG) systems, including 1) Detection and estimation of power quality; 2) Modeling; 3) Harmonic control for DG systems and microgrids; 4) Stability improvements for microgrids. Different power quality phenomena and solution were studied in the included papers, such as harmonics, resonance, frequency deviation, voltage sag, and fluctuation. From a network point of view, some papers studied the harmonic and stability issues in standalone microgrids which are more likely to cause power quality problems. Other papers discussed the power quality problems in microgrids which are weakly interconnected with the main distribution grid. In view of the published papers, there is a trend that increasingly advanced modeling, analysis, and control schemes were applied in the studies. Moreover, the latest works focus not only on single-unit problems but also multiple units or network issues. Although some of the hot topics are not included, this book covers multiple aspects of the current power quality research frontier, and represents a particularly useful reference book for frontier researchers in this field.